Tyrosine Kinase-Dependent Defense Responses Against Herbivory in Arabidopsis - Miyamoto, Takumi; Uemura, Takuya; Nemoto, Keiichirou; Daito, Maho; Nozawa, Akira; Sawasaki, Tatsuya; Arimura, Gen-ichiro (Frontiers in Plant Science, 2019)
Tyrosine (Tyr) phosphorylation is important for promotion of plants’ signaling. Arabidopsis calcium-dependent protein kinase related protein kinases (CRK2 and CRK3) phosphorylate Tyr residues of a subset of transcription factors, including herbivory-responsive ethylene response factor 13 (ERF13), but the in vivo functions of these kinases in plant defense responses and development remain to be clarified. We show that when CRKs were coexpressed with ERF13 in Arabidopsis leaf protoplasts, the transcription activity regulated via ERF13 was elevated by CRK2 but not CRK3 or their kinase-dead form mutants. Moreover, this elevation was abolished when a Tyr-phosphorylation mutant of ERF was coexpressed with CRK2, indicating that CRK2 serves as an effector of ERF13 mediated by Tyr-phosphorylation. Moreover, CRK2 and CRK3 acted as effectors of RAP2.6 and WRKY14, respectively. CRK-overexpressing lines and knockout mutants of Arabidopsis plants showed increased and decreased expression levels of the defensin gene PDF1.2 in leaves, respectively, conferring on the plants modulated defense properties against the generalist herbivore Spodoptera litura. However, these lines did not show any obvious developmental defects, indicating that CRKs play a role in defense responses but not in the ordinary growth or development of plants. Transcription of both CRK2 and CRK3 was positively regulated by jasmonate signaling and abscisic acid signaling upon herbivory. Our findings suggest that these phytohormone-responsive CRKs work coordinately for plant defense responses via Tyr phosphorylation of herbivory-responsive regulators.